2009
DOI: 10.1111/j.1365-2478.2009.00848.x
|View full text |Cite
|
Sign up to set email alerts
|

Developments in vibrator control

Abstract: Hydraulic limitations, non‐rigidity of the baseplate as well as variable characteristics of the ground constantly distort the downgoing energy output by vibrators. Therefore, a real time feedback control must be performed to continuously adjust the emitted force to the reference pilot signal. This ground force is represented by the weighted sum of the reaction mass and the baseplate accelerations. It was first controlled with an amplitude and phase locked loop system, poorly reactive and sensitive to noise. La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 8 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…They also suggested that a more suitable model to describe the vibrator–ground should be developed to understand the interaction between the vibrator and the ground. Boucard and Ollivrin (2010) provided a digital model of the vibrator to compute 10 states of the vibrator model related together by physical equations. An equivalent model was developed by Lebedev et al (2006) to analyze the nonlinear contact parameters based on the observed and predicted harmonic levels.…”
Section: Introductionmentioning
confidence: 99%
“…They also suggested that a more suitable model to describe the vibrator–ground should be developed to understand the interaction between the vibrator and the ground. Boucard and Ollivrin (2010) provided a digital model of the vibrator to compute 10 states of the vibrator model related together by physical equations. An equivalent model was developed by Lebedev et al (2006) to analyze the nonlinear contact parameters based on the observed and predicted harmonic levels.…”
Section: Introductionmentioning
confidence: 99%
“…In 1988, the first digital servo‐controlled vibrator electronics based on a numerical model of the vibrator and of the ground below the baseplate was introduced by Sercel (VE416; Garotta 1990; Boucard and Ollivrin 2010; Fig. 2).…”
Section: The Mid 1980s–early 1990smentioning
confidence: 99%
“…This method is simple and practical and widely used in the industry (Wei et al, 2010; Ziolkowski, 2010). Many researchers have demonstrated the complexity between the vibrator and ground (Dean et al, 2015; Ley et al, 2006; Martin and Jack, 1990) and suggested that the weighted sum method is not a good estimation of the ground force (Boucard and Ollivrin, 2010; Rowse and Tinkle, 2016; Saragiotis et al, 2010; Wei, 2009b). So, some approaches are developed to describe the interaction of vibrator-ground system and improve the ground force, providing many innovative perspectives.…”
Section: Introductionmentioning
confidence: 99%